HOME-BASED PARENTAL INVOLVEMENT IN CHILDREN WITH AND CHILDREN WITHOUT INTELLECTUAL DISABILITIES IN TÜRKIYE - Öztürk, Naciye; Sucuoğlu, N. Bülbin; Avci, Kerem (International Journal of Child, Youth and Family Studies, 2025)
This study examines home-based parental involvement in children with and children without intellectual disabilities, with a particular focus on the factors influencing parental involvement in the activities and play of children. The data were collected from 223 mothers using the Parent Interview Form. The findings reveal that both parents engaged significantly more in activities with children who had intellectual disabilities than with children who did not. Mothers reported that, in general, they were more involved than the fathers were in their children’s activities and play. Family income, mothers’ education level, and the number of children at home were shown to be crucial factors in parental involvement. The results may guide interventionists as to which activities and types of play parents should be encouraged to participate in more with their children, especially those with intellectual disabilities. Key points are: (a) parents of children with intellectual disabilities demonstrated greater involvement than did parents of children without disabilities; (b) the most common activity among parents of children with intellectual disabilities was going out with their children while reading aloud was the least common; (c) physical play was preferred by parents of children with intellectual disabilities and by fathers of children without disabilities; and (d) a noteworthy correlation exists between the frequency of parental involvement with children with intellectual disabilities and two key factors: the number of children in the family and the mother’s education level.